Closing the gap: The approach of optical and computational microscopy to uncover biomembrane organization - Eggeling, C; Honigmann, A (Elsevier, 2016)
Biological membranes are complex composites of lipids, proteins and sugars, which catalyze a myriad of vital cellular reactions in a spatiotemporal tightly controlled manner. Our understanding of the organization principles of biomembranes is limited mainly by the challenge to measure distributions and interactions of lipids and proteins within the complex environment of living cells. With the recent advent of super-resolution optical microscopy (or nanoscopy) one now has approached the molecular scale regime with non-invasive live cell fluorescence observation techniques. Since in silico molecular dynamics (MD) simulation techniques are also improving to study larger and more complex systems we can now start to integrate live-cell and in silico experiments to develop a deeper understanding of biomembranes. In this review we summarize recent progress to measure lipid-protein interactions in living cells and give examples how MD simulations can complement and upgrade the experimental data. This article is part of a Special Issue entitled: Biosimulations edited by Ilpo Vattulainen and Tomasz Róg.